The breadth of viruses in human semen - Salam, A; Horby, P (Centers for Disease Control and Prevention, 2017)
Zika virus RNA is frequently detected in the semen of men after Zika virus infection. To learn more about persistence of viruses in genital fluids, we searched PubMed for relevant articles. We found evidence that 27 viruses, across a broad range of virus families, can be found in human semen.